Implementation of sinusoidal pulse width modulation based on cordic algorithm using silterra 0.18um CMOS technology / Nurul Hidayah Marzuki - Marzuki, Nurul Hidayah (2009)
This thesis presents the implementation of Sinusoidal Pulse Width Modulation (SPWM) using Silterra 0.18um technology and it is based on CORDIC algorithm. The SPWM technique is used to control switches such as Insulated Gate Bipolar Transistor (IGBT) in major AC appliances. Synopsys tool is used to synthesize the Verilog Hardware Description language (HDL) model of the SPWM to its ASIC form. The use of Coordinate Rotation Digital Computer (CORDIC) in the source code make it provides an area-efficient architecture for effective design at Silterra 0.18um CMOS technology.